1983
DOI: 10.1111/j.1476-5381.1983.tb09365.x
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen blocks postsynaptic inhibition but not the effect of muscimol in the olfactory cortex

Abstract: 1The olfactory cortex slice preparation from the guinea-pig brain was used to study the effects of baclofen on inhibition using intracellular recording. Stimulation of the lateral olfactory tract activates sequentially excitatory and inhibitory pathways. Inhibition is manifest as a period of increased membrane conductance (termed postsynaptic inhibitory conductance, IPSC).2 Bath application of baclofen (0.2-50011M) reversibly blocked the IPSC. Baclofen also produced a secondary increase in the amplitude and du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…Consequently less Ca2+ would penetrate the cells, so reducing the efficiency of the excitationsecretion coupling. Our finding that the basal release declines by about 25% in the presence of (-)-baclofen argues in favour of such an interpretation: minimum changes of firing rate and alterations of Ca2+-dependent action potentials being observed in other preparations (see Dunlap, 1981;Scholfield, 1983). In principle, when tested against the Ba2+ stimulus, one would predict an equivalent decrease in hormone output (also reflecting the average firing rate).…”
Section: Discussionmentioning
confidence: 85%
“…Consequently less Ca2+ would penetrate the cells, so reducing the efficiency of the excitationsecretion coupling. Our finding that the basal release declines by about 25% in the presence of (-)-baclofen argues in favour of such an interpretation: minimum changes of firing rate and alterations of Ca2+-dependent action potentials being observed in other preparations (see Dunlap, 1981;Scholfield, 1983). In principle, when tested against the Ba2+ stimulus, one would predict an equivalent decrease in hormone output (also reflecting the average firing rate).…”
Section: Discussionmentioning
confidence: 85%
“…(-)-Baclofen may also produce postsynaptic effects caused either by an increase of potassium conductances (Newberry & Nicoll, 1984;Gaihwiler & Brown, 1985;Lacey, Mercuri & North, 1988) or by an inhibition of calcium currents (Dunlap, 1981;Dolphin & Scott, 1987). Finally, (-)-baclofen depresses Cl--mediated, bicuculline-sensitive inhibitory postsynaptic potentials in various central neurones (Scholfield, 1983;Misgeld, Klee & Zeise, 1986).…”
mentioning
confidence: 99%
“…That baclofen reduces stimulation-evoked GABAergic inhibition in the olfactory cortex and the hippocampus was suggested from extracellular recordings of field potentials [6,24]. Intracellular studies in vitro have shown that baclofen reduces the amplitude of short-latency GABAA receptor-mediated IPSPs evoked in various hippocampal neurons [14, 60,73], neurons in the olfactory cortex [96], and neurons in the frontal neocortex [55,56,102]. These depressions of IPSP amplitudes are not due to the concomitant action of baclofen to hyperpolarize these neurons.…”
Section: Actions Of Baclofen and Synaptic Transmissionmentioning
confidence: 99%
“…Short-latency IPSPs in rat neocortical neurons are also GABAA receptor-mediated [100,101], and baclofen's depressions of these IPSPs were independent of membrane potential between values of -50 and -110 mV [56]. Importantly, baclofen's reductions of short-latency GABAergic IPSPs in olfactory cortical and neocortical neurons were shown to be accompanied by reductions in the conductance increases measured during these IPSPs [56,96]. Because baclofen does not reduce responses to exogenously applied GABA or muscimol in these same neurons (see below), a postsynaptic blockade of the IPSP conductance can be excluded and these results argue strongly that baclofen reduces GABAA receptor-mediated IPSPs by a presynaptic action.…”
Section: Actions Of Baclofen and Synaptic Transmissionmentioning
confidence: 99%
See 1 more Smart Citation